Teknik Mind Mapping terhadap Kemampuan Menulis Teks Laporan Hasil Observasi Kelas VIII : The Mind Mapping Technique for Writing Observation Report Texts for Class VIII - Yustika Sari; Rina Devianty (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Many students struggle to write systematic observation reports due to a weak understanding of text structure and idea development techniques. Based on these problems, this study aims to analyze the effect of implementing mind mapping techniques as an alternative writing learning strategy. The study used a quantitative approach, a quasi-experimental design, and a Nonequivalent Control Group design. Two classes were included as samples: class VIII-4 (experimental) and VIII-5 (control). In the learning process, mind mapping techniques were used in the experimental class, while the control class used a conventional approach. Data were obtained from writing tests and then analyzed using statistical tests. The pretest results showed that the initial abilities of both groups were relatively balanced (control 67.4 and experimental 67.12).Meanwhile, the posttest scores showed a higher increase in the experimental class (80.89) compared to the control class (77.07). These findings indicate that using mind mapping positively impacts students' writing skills, especially in identifying main ideas and organizing texts systematically. This study implies that mind mapping can be an effective alternative learning strategy in junior high schools.